Classroom teaching and athletic coaching: Connecting social positions through interrole symbiosis. Issue 1 (2nd January 2021) - Brown, Alan; Wilson, Elizabeth K.
ABSTRACT: The purpose of this study is to examine a first-year educator's socialization into the roles of classroom teaching and athletic coaching. This case study explores the significance of a middle school social studies teacher's previous life experiences on her orientation toward teaching and coaching and the impact of her socialization – including teacher education, coaching education, and school induction – on her emerging teacher identity. Findings add to the existing research on interrole conflict among teacher-coaches while establishing a revised framework for interrole symbiosis, a concept that allows for the addition of interrole complementarity between the social positions of classroom teaching and athletic coaching in K-12 schools.